2009
DOI: 10.1109/tasc.2009.2018070
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Wind-and-React Bi-2212 Accelerator Magnet Technology

Abstract: Abstract-We report on our progress in the development of the technology for the application of Bi2Sr2CaCu2O8+x(Bi-2212) in Wind-and-React accelerator magnets. A series of superconducting subscale coils has been manufactured at LBNL and reacted at the wire manufacturer SWCC. Selected coils are impregnated and tested in self-field, even though the coils exhibited leakage during the partial melt heat treatment. Other coils have been disassembled after reaction and submitted to critical current (Ic) tests on indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…At this time the best conventionally processed Bi-2212 wires attain engineering current densities which exceed ∼400 A mm −2 at 4.2 K and 12 T (∼1400 A mm −2 in the superconductor) [4], about a factor of two below Nb 3 Sn conductors for which the superconductor J c can attain 2500-3000 A mm −2 . Whether the Bi-2212 performance limits are still capable of strong enhancement is thus of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time the best conventionally processed Bi-2212 wires attain engineering current densities which exceed ∼400 A mm −2 at 4.2 K and 12 T (∼1400 A mm −2 in the superconductor) [4], about a factor of two below Nb 3 Sn conductors for which the superconductor J c can attain 2500-3000 A mm −2 . Whether the Bi-2212 performance limits are still capable of strong enhancement is thus of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Fields >30 T are reachable with Bi-2212 magnets [1], which is well beyond the 24 T field limit reachable with Nb 3 Sn magnets. The round wire geometry makes the Bi-2212 conductors especially interesting for high energy physics applications where Rutherford cables are preferred for race track windings [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…High T c superconductor Bi 2 Sr 2 CaCu 2 O 8-x (Bi-2212) wire has demonstrated many attractive features, such as high irreversibility field (B irr > 100 T), isotropic electromagnetic performance, solenoid layer winding, and compatibility with conventional cabling and strand insulation methods. All of these advantages make it easy to adapt the well established Nb 3 Sn technology and make Bi-2212 one of most promising materials to enable superconducting magnets > 25 T range [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been already demonstrated that such properties make Bi-2212 a very competitive conductor for high field applications (> 20 T) such as magnets for nuclear magnetic resonance or accelerators [4][5][6][7][8][9], however, in this context, an enhancement of J C of two or three times seems to be still needed to boost the successful use of this superconductor in such applications. This aim has driven the work of several groups, especially in USA -where, besides the research labs, Oxford Superconducting Technology (OST) is a company leader on Bi-2212 round wire fabrication -and in Japan and Korea.…”
Section: Introductionmentioning
confidence: 99%